Efficacy of Fluoride Varnishes with Added Calcium Phosphate in the Protection of the Structural and Mechanical Properties of Enamel. (7th December 2017) - Shahmoradi, Mahdi; Hunter, Neil; Swain, Michael
Abstract : The aim of this study was to investigate the efficacy of various fluoride varnishes in the protection of the structural and nanomechanical properties of dental enamel. Demineralized enamel specimens were imaged using a high-resolution micro-CT system and lesion parameters including mineral density and lesion depth were extracted from mineral density profiles. Nanoindentation elastic modulus and hardness were calculated as a function of penetration depth from the load-displacement curves. The average depth of the lesion in specimens with no prior fluoride varnish treatment was 86 ± 7.1 9   μ m whereas the varnish treated specimens had an average depth of 67 ± 7.03   μ m (P < 0.05 ). The mineral density of enamel lesions with no fluoride varnish treatment had an average of 1.85 gr/cm3 which was 25% lower than the corresponding value in varnish treated enamel and 37% lower than sound enamel. While, in the varnish treated group, elastic modulus and hardness values had decreased by 18% and 23%, respectively, the corresponding values in the non-varnish treated specimens had a reduction of 43% and 54% compared to the sound enamel. The findings from this study highlight the preventive role of fluoride varnishes. Addition of calcium and phosphate does not seem to enhance or inhibit the prevention or remineralization performance of fluoride varnishes.